2014
DOI: 10.1080/10498850.2013.827767
|View full text |Cite
|
Sign up to set email alerts
|

Fish Processing By-Products as a Potential Source of Gelatin: A Review

Abstract: The current practice of fish processing generates large amounts of byproducts, which can account for up to three-quarters of the total fish weight. Despite the presence of several valuable components in the fish processing discards, the latter are usually dumped into landfills or at sea, having potentially harmful environmental effects or end up as low commercial value products (e.g. white fish meal). Still, fish processing byproducts can be considered as an alternative raw material for the preparation of high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
79
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 110 publications
(148 reference statements)
0
79
0
4
Order By: Relevance
“…Both color and odor do not affect the physical properties of gelatin (i.e., gel strength, viscosity, melting point, etc.). However, it is important for gelatin preparations incorporated in food systems not to impart any strong color or odor besides improving their functional properties (Karayannakidis and Zotos ). In the present study, the gelatin extract obtained after activated carbon treatment showed a light yellowish hue similar to that of bovine skin gelatin and was odorless.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both color and odor do not affect the physical properties of gelatin (i.e., gel strength, viscosity, melting point, etc.). However, it is important for gelatin preparations incorporated in food systems not to impart any strong color or odor besides improving their functional properties (Karayannakidis and Zotos ). In the present study, the gelatin extract obtained after activated carbon treatment showed a light yellowish hue similar to that of bovine skin gelatin and was odorless.…”
Section: Resultsmentioning
confidence: 99%
“…The second most important physical property of a gelatin preparation is viscosity (Karayannakidis and Zotos ). Yellowfin tuna skin gelatin showed a viscosity of 4.86 ± 0.06 cP, which was very similar to the viscosity of bovine skin gelatin (4.95 ± 0.21 cP; P ≥ 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…The undisputed protein fragments, present in gelatin preparations, are the α ‐ (monomer), β ‐ ( α ‐chain dimer) and γ ‐ ( α ‐chain trimer) chains with an approximate molecular weight (MW) of 100, 200 and 300 kDa, respectively (Eysturskard et al . ; Karayannakidis and Zotos ). Numerous studies in this field have shown that besides the aforementioned protein fragments, gelatins comprise of additional proteins and peptides with MW > 300 kDa and/or <100 kDa (Gómez‐Guillén et al .…”
Section: Resultsmentioning
confidence: 97%
“…However, since the occurrence of livestock disease outbreaks and because of several religious restrictions, a growing market demand for alternative sources of gelatin has emerged (Wasswa et al . ; Karayannakidis and Zotos ). Over the last decade, fish processing byproducts (e.g., skins, heads, bones, scales, swim‐bladders etc.)…”
Section: Introductionmentioning
confidence: 97%
“…However, because of safety and environment concerns, as well as industrial needs, citric acid could be of interest as it can be used together with hot water in fish bone gelatin extraction. Many researchers tried to extract fish bone and skin gelatin using a safer solvent (Karayannakidis and Zotos 2016). This research aimed to extract fish bone gelatin from Pa-ngasius catfish using pineapple liquid waste.…”
Section: Introduc Onmentioning
confidence: 99%